Effect of Icodextrin Solution on the Preservation of Residual Renal Function in Peritoneal Dialysis Patients: A Randomized Controlled Study. Issue 13 (March 2016) - Chang, Tae Ik; Ryu, Dong-Ryeol; Yoo, Tae-Hyun; Kim, Hyung Jong; Kang, Ea Wha; Kim, Hyunwook; Chang, Jae Hyun; Kim, Dong Ki; Moon, Sung Jin; Yoon, Soo Young; Han, Seung Hyeok; ,
Abstract : Abstract: Although icodextrin solution has been highlighted in the fluid management compared to glucose-based solutions, proof of a beneficial effect of icodextrin solution on residual renal function (RRF) is lacking. We conducted a multicenter prospective randomized controlled open-label trial to investigate whether icodextrin solution can preserve RRF. One hundred patients with urine volume ≥750 mL/day from 8 centers in Korea were randomly assigned to receive 1 exchange of icodextrin solution for a ≥8 hour-dwell time and 2 exchanges of 1.5% glucose-based biocompatible neutral pH solution or 1 exchange of ≥2.5% and 2 exchanges of 1.5% glucose-based biocompatible solutions. Using mixed-effects general linear models, we analyzed changes in residual glomerular filtration rate (GFR) and daily urine volume at 1 year. Forty-nine patients were assigned to the icodextrin group and 51 to the glucose solution group. During follow-up, the slope of the decline in residual GFR was −0.170 mL/min/month/1.73 m 2 in the icodextrin group, while it was −0.155 mL/min/month/1.73 m 2 in the glucose solution group (95% confidence interval [CI], −0.06 to 0.10; P  = 0.701). Daily urine volume decreased faster in the glucose solution group than in the icodextrin group (−31.02 vs −11.88 mL per month; 95% CI, −35.85 to −2.44; P  = 0.025). Results were consistent when we analyzed using intention-to-treat and per protocol principles. There were no differences in fluid status, peritoneal ultrafiltration, and peritoneal transport between groups during follow-up. This study clearly showed that icodextrin solution preserves residual urine volume better than glucose solution.